HAZARD ANALYSIS CRITICAL CONTROL POINT (HACCP) ON PALUMARA FISH SOUP IN THE NUTRITION INSTALLATION OF THE REGIONAL GENERAL HOSPITAL, INDONESIA - Yunancy, Sri; Nurlaela, Euis; Rusli, Rahmatunna (YCAB Publisher & IAKMI SULTRA, 2020)
Background: One of the government efforts in Indonesia to protect consumers and producers of healthy and safe food is to enforce the Republic of Indonesia's Law No. 23 of 1992 concerning Health (Part Four: Safety of Food and Beverages). Therefore, designing the HACCP design at the hospital is necessary to ensure food safety.Objective: This study aimed to find out how the design is appropriate for the food safety system with the HACCP Principles Approach in the Palumara Fish Soup Processing in the Nutrition Installation of the Kendari City Regional General Hospital, Indonesia.Methods: This study was descriptive with a qualitative approach conducted on 15-17 July 2019 with Palumara fish soup samples observed three times in the third menu cycle.Result: The critical points in the processing of Palumara fish soup include improper foodstuffs, washing of impurities in the tools and foodstuffs, boiling and stirring (the level of food maturity), stripping (i.e., the inedible part), and contamination from workers and containers.Conclusion: The nutrition installation at the Kendari City Regional General Hospital has not implemented Good Manufacturing Practices (GMP) as a whole, both from manpower, buildings, sanitation facilities and equipment. In addition, the hospital has not implemented HACCP in the food processing process, from the reception to distribution stage, so there are risks and dangers in Palumara fish soup.